Pulmonary function profile of children with sickle cell disease - Tambe, Mohankumar K. (International Journal of Research in Medical Sciences, 2017)
Background: Lung disease is a major cause of morbidity and mortality in sickle cell disease (SCD). In view of severe anemia, decreased blood oxygen affinity, pulmonary arterial vaso-occlusion, microinfarction and microfibrosis being associated with sickle cell disease; an analysis of pulmonary function in them will be of great interest. Methods: Seventy 6-12 years old children with SCD (SS pattern) were studied as cases along with age, sex and socioeconomic status matched 70 controls (AA pattern) and comparisons drawn between the two groups. Results: All the static and dynamic pulmonary functions such as FVC, FEV1, MMEFR25-75%, PEFR and MVV were found reduced in sickle cell disease, most of them significantly. Conclusions: Any restrictive, obstructive or combined pattern may be produced in SCD depending upon frequency & severity of the acute chest syndrome and vaso-occlusive crises in past.